The Suppression of Adjuvant-induced Inflammation and the Inhibition of the Serum and Tissue IL-17, TNF-α and IL-1β levels by Thymol and Carvacrol - Nasser Gholijani; Zahra Amirghofran* (Lorestan University of Medical Sciences, 2017)
Background and Aim: Thymol and carvacrol are two important components of thyme that have multiple medicinal uses. This study investigates the in vivo effects of these natural products on adjuvant-induced inflammation and secretion of interleukin (IL)-17 and key inflammatory cytokines in rats. Materials and Methods: We injected complete Freund's adjuvant (CFA) into the hind paws of rats in order to induce inflammation. Each of the CFA-treated rat groups received gavages of thymol, carvacrol, or vehicle (CFA-only group). Rats' paws and ankle edema were measured and then we were able to determine an inflammatory score based on the results. After 72 h of inflammation induction, sera were collected and subsequently inflamed tissue extracts were prepared for cytokine assay by ELISA. Results: Both components significantly decreased paw edema in rats (p<0.01). Thymol decreased ankle edema to 61.6% of edema in CFA-only rats (p<0.001). We observed a decreased inflammatory score in the thymol and carvacrol-treated rats. The evaluation of the tissue and serum inflammatory cytokine levels showed that both components decreased tumor necrosis factor (TNF)-α levels (p<0.05). Thymol and carvacrol reduced interleukin (IL)-1β serum and tissue levels, respectively. These components reduced tissue levels of IL-17 from 148.4±13.4pg/ml in CFA-only rats to 90.1±18.9pg/ml (thymol) and 82.3±9.2pg/ml (carvacrol). Both components decreased serum IL-17 levels in rats (p<0.05). In comparison, the anti-inflammatory drug, indomethacin, reduced the inflammatory score and decreased tissue TNF-α and IL-1β levels but did not affect IL-17 production. Conclusion: Carvacrol and thymol could relieve inflammation symptoms possibly by downregulating serum and tissue IL-17 expression in addition to key pro-inflammatory cytokines, TNFα and IL-1β.